Risedronate's Role in Reducing Hip Fracture in Postmenopausal Women with Established Osteoporosis - Brian J. Gates (Clinical Medicine Insights: Arthritis and Musculoskeletal Disorders, 2012)
Osteoporosis is a significant concern for postmenopausal women and is a critical factor in hip fracture. Examining evidence for osteoporosis medications in hip fracture is important for optimizing treatment. Purpose Review risedronate's role for hip fracture in postmenopausal women. Methods A literature search was conducted using Medline and Web of Science. The search was limited using the terms “risedronate” and “hip fracture,” and to studies that included women. Similar articles linked to the search and pertinent articles in bibliographies were also examined. Results Risedronate has demonstrated efficacy and cost effectiveness for hip fracture, but may not be beneficial for patients with low fracture risk. Risedronate is generally well tolerated, but may cause side effects in some patient populations. Conclusion Risedronate has benefit for hip fracture, but patients should be carefully screened to determine the appropriateness of risedronate before starting treatment.